Implikasi Ekonomi Kebijakan Fiskal di Masa Khalifah Utsman dan Ali - Febiola, Putri; Putri, Riche Hendriko; Pasaribu, Riyan Listianto; Hidayat, Faisal; Widianita, Rika (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2024)
This study aims to analyze the fiscal policies implemented during the leadership of Uthmanl bin Affanl and Alil bin Abil Talib. The specific objectives of this study are, (1) to identify the fiscal policy applied, (2) to analyze the impact of fiscal policy on the country's economy at that time, and (3) to explore the factors that influenced the choice of fiscal policy by the two caliphs. The research method used is qualitative with a descriptive approach. Data analysis was carried out using the content analysis method. The results of this study show that Uthman bin Affan's fiscal policy is based on sharia principles such as zakat, kharaj, jizyah, and usyur. Uthman also improved the zakat system and managed Baitul Mal with the principle of virtue. Meanwhile, Caliph Ali bin Abi Talib improved the administrative system of Baitul Mal and established taxes for land owners and fresh vegetables. He also minted coins for the Islamic State. Both have a positive impact on the economy and the welfare of the Muslim community.